Exploring Developmental Care in Neonatal Jaundice Management: A Case Report with Supporting Literature Synthesis - Esther Aduramo; Deborah T. Esan; Emmanuel Adesuyi; Opeoluwa Olabode; Elizabeth Awoniyi; Blessed Oyama; Oluwadamilare Akingbade (Journal of Pediatrics Review)
Background: Neonatal jaundice is highly predominant among preterm neonates and its effective management is essential to reducing hospital admission duration and the associated financial burden. Phototherapy remains the primary choice of management; however, the incorporation of developmental care and parental involvement has led to enhanced outcomes. Case Presentation: This case report presents “Baby M,” a preterm female neonate born at 32+5 weeks gestation due to maternal complications, including anemia and pregnancy-induced hypertension, who was admitted to a neonatal unit with prematurity, ventriculomegaly and bilateral talipes. Upon admission, she required high-flow oxygen therapy for mild respiratory distress and intravenous antibiotics for suspected sepsis. Her serum bilirubin levels reached 236 µmol/L, exceeding the treatment threshold defined by the National Institute for Health and Care Excellence guidelines, leading to the initiation of phototherapy. Initially placed on intravenous fluids due to respiratory challenges, Baby M was later transitioned to expressed breast milk from her mother. Her phototherapy treatment followed National Institute for Health and Care Excellence guidelines, ensuring that parental involvement and neurodevelopmental support were prioritized to minimize stress and promote optimal outcomes. This report highlights the benefits of developmental care in care in reducing stress, promoting bonding and optimizing neurodevelopment in preterm neonates, underscoring its importance in improving therapeutic outcomes in neonatal jaundice. Conclusions: The components of developmental care are effective and should therefore be incorporated into the management of neonatal jaundice, for improved therapeutic outcomes.